Sociodemographic and reproductive factors of female prisoners = Situação socioeconômica e reprodutiva de mulheres presidiárias - Rodrigues Barros, Maria Aline (2016)
Objective: To describe the socioeconomic and reproductive profile of female prisoners. Method: The sample consisted of 47 female inmates of penitentiaries and Teresina peaks. For data collection a form prescribed by the researcher was used. Data were collected from July to August 2013, which were tabulated and analyzed using the Statistical Package for the Social Sciences (SPSS) version 20.0. Results: Showed a profile of young, unmarried women, who exercised occupation that required little skill, low education and income. Regarding reproductive health, 42,5% were multiparous, and 40,4% had less than six visits. The abortion rate was high, 42,5%. Conclusion: There was a need to plan educational strategies to prevent injuries to sexual and reproductive health of prisoners, being essential to the development of tactics to break down educational barriers and generate behavior change and promote self-care.